STATE OF ENGINEERING IN UKRAINE THROUGH THE PRISM OF RESOURCE MANAGEMENT - ABUSHOV, Teymur (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Mechanical engineering is one of the main branches of industry in Ukraine. As a result of the full-scale invasion, the production capacities of some enterprises were destroyed. Another group of enterprises relocated to safer regions. In contrast to industry in general and processing industry in particular, during the two years of the war, manufacturers did not reduce, but increased the volume of production and sale of products. In the first year of the war, there was a drop in production volumes of sub-sectors, but in the following period, manufacturers of motor vehicles and computers, electronic and optical products achieved a significant increase in volumes. It is worth noting that the production of motor vehicles provided the largest volumes of product sales in terms of value. In the nine months of 2023, about 79% of the industry’s enterprises made a profit. The fewest enterprises that had a negative financial result were among the manufacturers of computers, electronic and optical products. In addition, machine-building enterprises had better indicators of profitability of economic activity in general and operational activity in particular compared to indicators of industry. The industry received opportunities for development during the war period due to the presence of a state defense order. However, maintaining production growth and achieving economic efficiency in the future is possible only with the formation of an integrated approach to resource management. This is especially relevant against the background of the energy crisis, the shortage of labor resources, the lack and instability of financial income.